2022
DOI: 10.3390/sexes3010005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Receptivity Signal of Lordosis Posture and Intra-Sexual Competition in Women

Abstract: Previous research has shown that women may use self-enhancement strategies to compete with one other. Lumbar curvature in women is considered to enhance a woman′s attractiveness, potentially due to its role in bipedal fetal load and sexual receptiveness. The current study investigated the role of lumbar curvature on women’s perceptions of sexual receptiveness as well as its role in women’s intrasexual competitiveness. Study 1 (N = 138) tested and confirmed that women’s intrasexual competition influences their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In general, an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [53]. It can be said that the higher incidence of hyperkyphosis in men may be a clinical sign of the presence of osteoporosis and a potentially modi able risk factor for adverse health consequences [54]. Our study also con rmed a higher incidence of hyperkyphosis in students (30.77%) than in female students (10.00%).…”
Section: Discussionsupporting
confidence: 74%
“…In general, an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [53]. It can be said that the higher incidence of hyperkyphosis in men may be a clinical sign of the presence of osteoporosis and a potentially modi able risk factor for adverse health consequences [54]. Our study also con rmed a higher incidence of hyperkyphosis in students (30.77%) than in female students (10.00%).…”
Section: Discussionsupporting
confidence: 74%
“…While the above features are under the control of women, other features for which they have far less control have also been extensively studied, including waist to hip ratio (WHR), overall body mass index (BMI), lumbar curvature, and facial shape and size (Cornelissen et al, 2009; Dixson et al, 2010; Pazhoohi et al, 2022; Valenzano et al, 2006). Breast features have also been extensively studied, including breast size, breast ptosis, and areola pigmentation (Dixson et al, 2010; Dixson et al, 2011a; Dixson et al, 2011b; Dixson et al, 2015; Garza et al, 2021; Groyecka et al, 2017; Pazhoohi et al, 2020; Swami & Tovée, 2013).…”
mentioning
confidence: 99%
“…A study by Jankowicz-Szymańska et al [ 52 ] demonstrated that hyperlordosis is characteristic for young female students, while hypolordosis is characteristic for older women. In general, an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [ 53 ]. It can be said that the higher incidence of hyperkyphosis in men may be a clinical sign of the presence of osteoporosis and a potentially modifiable risk factor for adverse health consequences [ 54 ].…”
Section: Discussionmentioning
confidence: 99%